Effects of consuming purslane seed powder on indicators of metabolic syndrome in women: a randomized clinical trial - Papoli, Maryam; Pishdad, Samaneh; Nadjarzadeh, Azadeh; Hosseinzadeh, Mahdieh (Progress in Nutrition, 2019)
Introduction: The aim of this study was to investigate the effect of purslane seed powder on indicators of metabolic syndrome in women with this syndrome. Materials & Methods: In this study, 64 middle-aged women (30-59 years old) with metabolic syndrome were randomly divided into two groups. The intervention group received 10 grams purslane seed powder combined with 150cc low fat yogurt daily for 12 weeks. The control group received only 150cc low fat yogurt daily for 12 weeks. At the first and at the end of the study, the height, weight, BMI, waist and biochemical indices such as LDL, HDL, TG, FBS and the blood pressure of all of participants were measured. Findings: The average age of the participants was 42.8 year. After consuming the purslane, there was significant decrease in weight (-1.07 versus 0.06 kg, p